Investigation of the Interaction of Polar Molecules on Graphite Surface: Prediction of Isosteric Heat of Adsorption at Zero Surface Coverage - Fan, Wu (2017)
The interactions of polar molecules with various orientations on graphite surface are calculated employing molecular simulation under static conditions in which the multiple-sites Lennard-Jones (LJ), electrostatic, and dipole induction potentials are considered. The Henry’s constant and the potential energy as a function of polar molecule–graphite separation distance (z) are used to calculate the isosteric heat of adsorption at zero surface coverage (qsto), and the results are compared to experimentally measure qsto data of various polar molecules such as water, ammonia, methanol, and ethanol + graphite systems. The maximum qsto values are observed for the z values ranging from 2.5 to 4 Å with respect to various polar molecule orientations. The LJ potential contributes more than 90% and the induction potential adds less than 10% of total potentials at the maximum potential well depth, whereas the electrostatic contributions are found to be less than 1% of total potential energy. It is also found that the induction potential increases exponentially for the separation distance decreasing from 3 to 0 Å for all polar molecules presented in this Article.